Georges Didi-Huberman, Écorces, and Otto Dov Kulka, Landscapes of the Metropolis of Death – as Lager essays? Imagination and remembrance of the title formulations in relation to the formulation “anus mundi” - Kuczyńska-Koschany, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article is an attempt at interpretation of two essays, which may be called „Lager” essays. These are Écorces written by G. Didi-Huberman and Landscapes of the Metropolis of Death written by O.D. Kulka, their books are deeply related as the negation or at least as the questioning of the title of autobiographical book Anus mundi written by W. Kielar. Both authors do not describe Nazi concentration camp as „the anus of the world”. Their imagination is a post-imagination, their memory is a post-memory. In her paper Kuczyńska-Koschany considers the condition of the essay as quasi-genre after the Holocaust, after the genocide and in reference to the experience of a Lager.